Anterior Cruciate Ligament Reconstruction with Autologous Hamstring Single- versus Double-Bundle Graft: A Prospective Study with 10-Year Follow-up - Yela-Verdú, Christian; Ares, Oscar; Albareda, Daniel; Oller, Bárbara; Sallent, Andrea; Jornet-Gibert, Montsant; Amillo, Juan R. (The Journal of Knee Surgery, 2022)
The purpose of the present study was to compare the clinical and subjective outcomes of anterior cruciate ligament (ACL) reconstruction using an autologous hamstring double bundle (DB) with a single bundle (SB) after a 10-year follow-up. A prospective comparative cohort study was performed of 47 consecutive patients with ACL rupture included between May 2006 and March 2008. Inclusion criteria were less than 2 years since the injury date, no previous surgery on the affected knee, and having closed growth plates. Patients were divided into two groups: (1) SB group (n = 25) and (2) DB group (n = 22). Patients underwent evaluation before surgery and at 1 and 10 years postoperatively. The clinical evaluation included the International Knee Documentation Committee (IKDC) Questionnaire, pivot shift test, and single hop test, as well as X-rays (anterior drawer X-rays on a Telos stress radiography). Range of motion (ROM) was assessed at 10-year follow-up. Both groups were similar in terms of baseline characteristics. Post hoc power analysis showed that among 30 and 226 patients would be needed for statistical significance, depending on the outcome. With the numbers available, no significant differences were observed in subjective IKDC, anterior stability (measured with Telos), and functional test outcomes (single hop test) between both groups at 1 and 10 years postoperatively. Regarding rotational instability (pivot-shift test), DB group was significantly superior (p = 0.002). Regarding ROM, no significant differences were observed between groups. No failure was registered in any of the groups. ACL reconstruction (ACLR) with an autologous hamstring, both with bundles and DB, shows overall better outcomes compared with the status before surgery. DB ACLR provides better rotational control of the knee, an outcome that is maintained after 10 years.
Keywords: anterior cruciate ligament; autologous hamstring; double bundle; single bundle; ACL reconstruction